Value of demand flexibility for providing ancillary services: A case for social housing in the Irish DS3 market. (December 2020) - Agbonaye, Osaru; Keatley, Patrick; Huang, Ye; Bani-Mustafa, Motasem; Ademulegun, Oluwasola O.; Hewitt, Neil
Abstract: This paper evaluates the potential of consumer flexibility from a portfolio of heat loads, solar panels and batteries in Social Housing to provide ancillary services. We propose two new ancillary service products: Turn-Up-Demand (TUD) and Turn-Down-Demand (TDD). We ran simulations for a complete year. The buffer-tank scenario provided earnings of £146/year for an average consumer. Finally, we propose a new policy called the Vulnerable Consumer Priority in Administering System Services (VCPASS) and the use of Heat-as-a-Service (HaaS) to fund the replacement of oil-boilers with heat pumps in fuel poor homes with a rate of 9.99p/kWh of heat for a payback period of 15 years. Highlights: Novel demand response simulation model is developed using real measurement data of heat pumps, solar panels, and the grid. First detailed investigation into the performance of demand response as a provider of operating and replacement reserves. Using thermal storage to provide ancillary services puts low carbon heat from heat pumps at the same cost as oil boilers. New Policy (VCPASS) to help fund the replacement of oil-fired heating with heat pumps in fuel poor homes. Recommendations for the introduction of residential demand response technology into the Irish DS3 market.